Pre-operative moderate cognitive impairments and their importance in cognitive dysfunction development in post-coronary bypass patients - O. A. Trubnikova; I. V. Tarasova; I. D. Syrova; I. N. Kukhareva; O. V. Maleva (Фундаментальная и клиническая медицина)
Aim. To determine the incidence and risk factors of postoperative cognitive dysfunction (POCD) after coronary bypass (CABG) in patients with pre-operative moderate cognitive impairment (MCI).Materials and Methods. Up to CABG two groups were formed, consisting of 50 patients with presence and 51 without MCI. Neuropsychological research (12 tests) was conducted up to CABG, on the 10th day and after 1 year. Early (10 days after surgery) and remote (1 year later) POCD were diagnosed with a 20 % decrease in the rate of 20% of tests.Results. Prior to CABG, they had a lower level of formation (p = 0.03), a lower fraction of the left ventricle ejection, (p = 0.02) and a more severe coronary tract lesion on the SYNTAX scale, (p = 0.01) than patients without MCI. Factors significant for the development of early POCD were the duration of with cardiopulmonary bypass (p = 0.035) and the severity of multi-organ insufficiency, rated on the SOFA scale (p = 0.04). In persons with pre-operative MCI, 72 % of cases were diagnosed with early POCD, 54 % with remote POCD, and 81 % with early POCD.Conclusion. Chronic heart failure with low rates of left ventricular ejection fraction, severe coronary artery damage and low levels of education contribute to the development of MCI in patients with ischemic heart disease. Pre-operational MCI is not the main cause of POCD. However, its presence and development in these patients of early POCD contributes to its retention a year after surgery.